Życzenie jako gatunek tekstu - Filip, Grażyna (Stylistyka, 2021)
Greetings and wishes comprehended as acts of etiąuette expressed at different occa- sions are the subject of the article. The author analyses wishes sent on post cards prepared for various occasions dating to the 20,h and 21st century. The point of reference for such expression are:1. local newspapers and magazines - the published ready wishes,2. electronic mail - electronic versions of cards for different occasions.The common feature of the above is the possibility of joining the graphic and the lan- guage codę as well as the possibility of sending the wishes on a massive scalę.The relationship between text and time is treated as the influence of time on the text of the wishes. The aim of the article is the observation whether the wishes undergo a change with the passing of time, for example in the course of the century, which aspects - styli- stic-language aspect or the universal hierarchy of values - undergo change and finally for which reasons.